2014
DOI: 10.1007/s00125-014-3334-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind the superior effects of interval vs continuous training on glycaemic control in individuals with type 2 diabetes: a randomised controlled trial

Abstract: Aims/hypothesis By use of a parallel and partly crossover randomised, controlled trial design we sought to elucidate the underlying mechanisms behind the advantageous effects of interval walking training (IWT) compared with continuous walking training (CWT) on glycaemic control in individuals with type 2 diabetes. We hypothesised that IWT, more than CWT, would improve insulin sensitivity including skeletal muscle insulin signalling, insulin secretion and disposition index (DI).Methods By simple randomisation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 50 publications
8
76
3
Order By: Relevance
“…The findings of associations of PAEE and CRF with peripheral insulin sensitivity are consistent with previous findings using objectively measured PAEE [38,39], including previous analyses on participants in the ADDITION-PRO cohort [22]. A recent randomised controlled trial showed that interval walking training improved insulin sensitivity more than continuous walking training, which further supports our finding of an association between CRF and insulin sensitivity independent of PAEE [40]. With regard to HOMA-IS, adjustment for CRF made the association between PAEE and HOMA-IS nonsignificant.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of associations of PAEE and CRF with peripheral insulin sensitivity are consistent with previous findings using objectively measured PAEE [38,39], including previous analyses on participants in the ADDITION-PRO cohort [22]. A recent randomised controlled trial showed that interval walking training improved insulin sensitivity more than continuous walking training, which further supports our finding of an association between CRF and insulin sensitivity independent of PAEE [40]. With regard to HOMA-IS, adjustment for CRF made the association between PAEE and HOMA-IS nonsignificant.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, Mitranun et al (Mitranun et al, 2014) reported that 12 weeks of treadmill exercise training comprised of 6, 1-minute intervals at approximately 85% of peak VO2 separated by 4-minute recovery intervals at approximately 60% of peak VO2, performed three times per week resulted in improved fasting glucose, homeostasis model assessment for insulin resistance (HOMA-IR) scores, and reductions in glycosylated hemoglobin (HbA1c) in adults with T2DM. Mechanisms whereby interval exercise enhances glucose control in this population include how intramuscular fat is partitioned (i.e., triacylglycerol vs diacylglycerol) (Schenk and Horowitz, 2007), enhanced insulin signaling, (Karstoft et al, 2014) improved defenses against oxidative stress, (Mitranun et al 2014) and reductions in inflammatory activity (Samaan et al, 2014). Although the participants in this study were young and healthy, the similarity of the responses elicited by both SHORT and LONG HIFT with those induced by more traditional modes of exercise makes it reasonable to suggest that responses in those with T2DM would also be similar, though further investigation is necessary to confirm this.…”
Section: Volume 12 | Issue 3 | 2017 | 717mentioning
confidence: 99%
“…Traditionally, these studies have examined bouts that are of short duration and high-intensity, while utilizing single modality intervals such as cycling or running (Adams, 2013). Despite the capacity of this type of exercise to improve fitness and metabolic function (Karstoft et al, 2014;Shaban et al, 2014;Little et al, 2011;Mitranun et al, 2014), this style often lacks appeal for participant adherence (Gillen and Gibala, 2013). Recently, trends in fitness have gravitated towards a style of exercise described as High-Intensity Functional Training (HIFT) (Thompson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have demonstrated that, compared to aerobic exercise, HIT is more effective at improving insulin resistance (Jelleyman et al, 2015) and V O2max (Milanovic et al, 2015) in healthy sedentary individuals. In T2D patients, HIT has been shown to be associated with improvements in insulin sensitivity (Karstoft et al, 2014), glycaemic control (Little et al, 2011), and endothelial function (Madsen et al, 2015). However, due to the required recovery periods in between high-intensity bouts, most available HIT protocols are not as time-efficient as often claimed (Gillen & Gibala, 2014), and even in submaximal HIT protocols the high number of high-intensity bouts per training session results in high perceived exertion (Little et al, 2011).…”
Section: Introductionmentioning
confidence: 99%